Dewan Pengawas Syariah Dan Pengungkapan Aspek Lingkungan, Produk Dan Jasa Pada Bank Syariah - Ari Purwanti (Jurnal Akuntansi dan Keuangan Islam, 2016)
This study aims to provide empirical evidence of the influence of the role of the Sharia Supervisory Board on the disclosure of environmental aspects and aspects of banking services product on Islamic banking in Indonesia based on Islamic Social Reporting in the annual report period 2013-2015. This study performed content analysis and simple regression. There are nine Islamic banks were selected in the study sample were tested. The results showed that the amount of the Sharia Supervisory Board has given a significant effect on the extent of disclosure of environmental aspects and also aspects of banking services products based on Islamic Social Reporting. However, the test results that show the influence of the frequency of the Sharia Supervisory Board meeting on the extent of disclosure of environmental aspects and aspects of banking products based Islamic Social Reporting that proved insignificant.